Development of a computerised fire alarm panel model / Ab. Aziz Yusof - Yusof, Ab. Aziz (1994)
This project is concerned on the development of a PC based fire alarm panel model that could later be deveoped into a high technology based fire alarm model. The study incorporates refabrication of the existing fire alarm panel circuits interfaced into a computer. Circuits are constructed modular in nature so as to provide a base for continuous development.